Angiotensin II Increases Endoplasmic Reticulum Stress in Adipose Tissue and Adipocytes - Menikdiwela, Kalhara R.; Ramalingam, Latha; Allen, London; Scoggin, Shane; Kalupahana, Nishan S.; Moustaid-Moussa, Naima (Scientific reports, 2019)
The Renin Angiotensin System (RAS), a key regulator of blood pressure has been linked to metabolic disorders. We have previously reported that adipose overexpression of angiotensinogen in mice (Agt-Tg) induces obesity, in part mediated by adipose tissue inflammation, through yet unidentified mechanisms. Hence, we hypothesize that adipose tissue enrichment of angiotensinogen leads to activation of inflammatory cascades and endoplasmic reticulum (ER) stress, thereby, contributing to obesity. We used wild type (Wt), Agt-Tg and Agt-knockout (KO) mice along with 3T3-L1 and human adipocytes treated with RAS, ER stress and inflammation inhibitors. ER stress and pro-inflammation markers were significantly higher in Agt-Tg compared to Wt mice and captopril significantly reduced their expression. Furthermore, in vitro treatment with Ang II significantly induced ER stress and inflammation, whereas angiotensin II receptor inhibitor, telmisartan reduced RAS effects. Moreover, miR-30 family had significantly lower expression in Agt-Tg group. MiR-708-5p and -143-3p were upregulated when RAS was overexpressed, and RAS antagonists reduced miR-143-3p and -708-5p in both mouse adipose tissue and adipocytes. Activation of RAS by Ang II treatment, increased inflammation and ER stress in adipocytes mainly via AT1 receptor, possibly mediated by miR-30 family, -708-5p and/or -143-3p. Hence, RAS and mediating microRNAs could be used as potential targets to reduce RAS induced obesity and related comorbid diseases.